2003
DOI: 10.1016/j.cub.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Connexin43 Expression Accelerates the Rate of Wound Repair

Abstract: The repair of tissue damage is a key survival process in all organisms and involves the coordinated activation of several cell types. Cell-cell communication is clearly fundamental to this process, and a great deal is known about extracellular communication within the wound site via cytokines. Here we show that direct cell-cell communication through connexin 43 (Cx43) gap junction channels also plays a major role in the wound healing process. In two different wound healing models, incisional and excisional ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
311
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(329 citation statements)
references
References 23 publications
15
311
2
1
Order By: Relevance
“…Several enzymes involved in metabolism were characterized, including ornithine decarboxylase antizyme, delta-6-fatty acyl desaturase, hexose-6-phosphate dehydrogenase, glucose phosphate isomerase A, branched chain alpha-keto acid dehydrogenase, and uridine phosphorylase. In addition, annexin A1 which involved in a diversity of cellular processes and connexin 43 in cell communication (Qiu et al 2003) have also been identified in the present study, and the latter is reported to have a major role in the process of wound healing (Qiu et al 2003).…”
Section: Discussionsupporting
confidence: 62%
“…Several enzymes involved in metabolism were characterized, including ornithine decarboxylase antizyme, delta-6-fatty acyl desaturase, hexose-6-phosphate dehydrogenase, glucose phosphate isomerase A, branched chain alpha-keto acid dehydrogenase, and uridine phosphorylase. In addition, annexin A1 which involved in a diversity of cellular processes and connexin 43 in cell communication (Qiu et al 2003) have also been identified in the present study, and the latter is reported to have a major role in the process of wound healing (Qiu et al 2003).…”
Section: Discussionsupporting
confidence: 62%
“…188 Several connexins appear to be expressed in the skin, including Cx43, found in the epidermis and dermis and the potential for targeting this connexin has been extensively researched. [189][190][191] Numerous antisense-based therapies targeting Cx43 are in development. 188 …”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%
“…Gap junctions are major channels that allow cells to communicate with one another by facilitating intercellular communication, including the transfer of Ca 2+ , a fundamental ion in keratinocyte differentiation, and small molecules of ,1 kDa -such as inositol triphosphate (IP 3 ) -between cells. In the skin, gap junctions appear to regulate a number of cellular processes, including wound healing, differentiation and barrier function (Goliger and Paul, 1995;Coutinho et al, 2003;Qiu et al, 2003;Djalilian et al, 2006;Mori et al, 2006;Man et al, 2007;Kandyba et al, 2008;Simpson et al, 2013), and their role in epidermal integrity is reviewed elsewhere (Martin et al, 2014).…”
Section: The Importance Of Gap Junctionsmentioning
confidence: 99%